13C Methacetin Breath Test for Assessment of Microsomal Liver Function: Methodology and Clinical Application. (5th July 2017) - Gorowska-Kowolik, Katarzyna; Chobot, Agata; Kwiecien, Jaroslaw
Abstract : Assessment of the liver function, and the need of constant monitoring of the organ's capacity, concerns not only patients with primary liver diseases, but also those at risk of hepatopathies secondary to other chronic diseases. Most commonly, the diagnostics is based on measurements of static biochemical parameters, which allow us to draw conclusions only indirectly about the function and the degree of damage of the organ. On the other hand, liver biopsy is an invasive procedure and therefore it is associated with a considerable risk of complications. Dynamic tests enable us to assess quantitatively the organ's functional reserve by analyzing the kinetics of the metabolization of the substrate by the liver. In practice applied are breath tests using substances such as aminopyrine, caffeine, methacetin, erythromycin (for assessment of the microsomal function); phenylalanine, galactose (for assessment of the cytosolic function); methionine, octanoate, ketoisocaproic acid (for assessment of the mitochondrial function). The test with 13 C methacetin belongs to the best described and most widely applied methods in noninvasive liver function assessment. Due to the rising availability of this method, knowledge concerning its limitations and controversies regarding the methodology, as well as its usefulness in chosen groups of patients, seems to be vital.